Factors Influencing the Popularity of Artificial Insemination of Mares in Europe † - Kowalczyk, Alicja (Animals (Basel), 2019)
SIMPLE SUMMARY: The popularity of mare insemination as an element affecting the dynamic growth of breeding progress among horses in Europe is subject to various fluctuations. The success of this method of reproduction should be considered first of all in terms of the quality of semen available on the market, the types of semen storage technology, the profitability of its use resulting from the effectiveness of insemination with the selected type of semen, and factors affecting the success of artificial insemination. The purpose of this work was to present the factors determining the popularity of artificial insemination of mares in Europe. The presented statistics show that the popularity of the use of chilled semen has gradually increased in the group of sport mares, while in the group of breeding mares, the popularity of frozen semen has increased. In the remaining group of mares (not classified as sport or breeding), insemination with chilled semen was dominant. To talk about the success of artificial insemination of horses in Europe, it is necessary to look thoroughly at these aspects that affect the popularity of this reproduction biotechnology, and in particular to improve the quality of insemination doses. ABSTRACT: The purpose of this review was to analyze factors affecting the popularity of artificial insemination of mares in Europe in the context of sperm quality. Taking into account the prices of stallion semen on the world market, efficiency is important for the profitability of its use in artificial insemination programs in Europe. To increase the efficiency of a semen insemination facility, it is necessary to correctly and objectively assess the quality of semen. The available range of tools allows an effective evaluation of the potential fertility of a stallion. For several years, artificial insemination programs in Europe have been gaining popularity. However, the frequency of chilled or frozen semen use is still quite low. This is mainly due to the common, negative opinion about the effectiveness of the use of packaged insemination doses as opposed to natural insemination. Unfortunately, the quality of the semen offered often deviates from expectations, which results in unsatisfactory (and therefore unprofitable) pregnancy rates. This review presents the popularity structure of chilled and frozen semen use in European horse breeding as well as the current state of research on the effectiveness of semen production technology. It is shown that the popularity of using chilled semen in the artificial insemination of mares in Europe has been gradually increasing in the group of sport mares, while in the group of breeding mares, in recent years, frozen semen has been gaining popularity. In the remaining group of mares (not classified as sport or breeding), insemination with chilled semen has been dominant.